A short review on the trend of mobile commerce continuance intention studies and its underlying model - Azyanee Luqman; Mohammad Ismail; Razli Che Razak (Universiti Malaysia Kelantan, 2013)
The purpose of this article is to provide a general overview on mobile commerce research with a focus on mobile commerce continuance usage intention studies. It highlights the phenomenon of mobile commerce industry as well as the conceptual definition of mobile commerce itself. It is then followed by a discussion on selected previous mobile commerce studies. In order to bridge the gap in the current literature, this paper offers significant implication in terms of understanding the need for conducting more research on mobile commerce continuance intention. This article reviews approximately seventy journal article on mobile commerce which are published from 2004 until 2014 from selected journal publications. A brief discussion on the underlying model for mobile commerce continuance usage intention studies follows suit.